Identifying and Evaluating Factors Affecting Financial Risk in Companies Admitted to the Tehran Stock Exchange - Mehdi Ahmadpour; Reza Aghajan Nashtaei; Mohsen Khodadadi (Environmental Energy and Economic Research)
Financial risk affects not only the growth and development of a company but also the economic development of the whole society. This research has been carried out to identify and investigate factors affecting financial risk in Tehran Stock Exchange companies. The statistical population of this research is all the companies admitted to the Tehran Stock Exchange, which have been active on the stock exchange from April 2012 to March 2021. This research is conceptual in terms of its purpose and descriptive and correlational research in terms of the data collection method. In this research, the required data has been extracted from the RAHAVARD software, the financial statements of the companies, and the Kodal website. IBM SPSS Statistics, Excel, and stata16 software were used for data analysis. The research results showed that liquidity risk, investment risk, activity risk, leverage risk, and valuation risk have a significant effect on the financial risk of Tehran Stock Exchange companies. In other words, financial risk is under the influence of liquidity, investment, activity, leverage, and valuation risks. Therefore, by using the results of this research, the managers of the companies can control the factors affecting the financial risk to prevent unfavorable results of the financial risk and thus improve their financial performance.